Proceedings of the Twenty-Eighth Annual ACM-SIAM Symposium on Discrete Algorithms 2017
DOI: 10.1137/1.9781611974782.140
|View full text |Cite
|
Sign up to set email alerts
|

A (2 + ∊)-Approximation for Maximum Weight Matching in the Semi-Streaming Model

Abstract: We present a simple deterministic single-pass (2 + )-approximation algorithm for the maximum weight matching problem in the semi-streaming model. This improves upon the currently best known approximation ratio of (3.5 + ).Our algorithm uses O(n log 2 n) space for constant values of . It relies on a variation of the local-ratio theorem, which may be of independent interest in the semi-streaming model.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 27 publications
0
58
0
Order By: Relevance
“…They showed that a modification of the greedy algorithm can find a 1/6 approximation of the maximum weighted matching in the semi-streaming model. This bound later improved in a series of works [17,21,5,4,18,10] to (1/2 − ǫ) approximation. A recent work by Gamlath et al [9] shows that when edges arrive in a random order, there exists a semi-streaming algorithm that finds a 1/2 + Ω(1) approximation of the maximum weighted matching, beating the 1/2 barrier for the weighted case.…”
Section: Related Workmentioning
confidence: 96%
“…They showed that a modification of the greedy algorithm can find a 1/6 approximation of the maximum weighted matching in the semi-streaming model. This bound later improved in a series of works [17,21,5,4,18,10] to (1/2 − ǫ) approximation. A recent work by Gamlath et al [9] shows that when edges arrive in a random order, there exists a semi-streaming algorithm that finds a 1/2 + Ω(1) approximation of the maximum weighted matching, beating the 1/2 barrier for the weighted case.…”
Section: Related Workmentioning
confidence: 96%
“…In contrast to unweighted graphs where the basic greedy algorithm gives a ( 1 /2)-approximation, it was only very recently that a ( 1 /2 − ε)-approximation streaming algorithm was given for weighted matchings [PS17]. The algorithm of Paz and Schwartzman is based on the local ratio technique, which we now describe 3 .…”
Section: Single-pass Streaming With Random Edge Arrivalsmentioning
confidence: 99%
“…The issue is that, if the edges arrive in an adversarial order, we may add all the edges to S. For dense graphs, this would lead to a memory consumption of Ω(n 2 ) instead of the wanted memory usage O(n poly(log n)) which is (roughly) linear in the output size. The main technical challenge in [PS17] is to limit the number of edges added to S; this is why that algorithm obtains a ( 1 /2 − ε)-approximation, for any ε > 0, instead of a ( 1 /2)-approximation.…”
Section: Single-pass Streaming With Random Edge Arrivalsmentioning
confidence: 99%
See 2 more Smart Citations